Agricultural policy developments in the EU pre-accession countries - Martinovska Stojcheska, Aleksandra,Kotevska, Ana,Janeska Stamenkovska, Ivana,Dimitrievski, Dragi,Zhllima, Edvin,Vaško, Željko,Bajramović, Sabahudin,Mustafa, Mihone Kerolli,Marković, Milan,Kovacević, Vlado,Koç, Ahmet Ali,Bayaner, Ahmet,Kasimēs, Charalampos,Pavloska Gjorgjieska, Dori (Publications Office of the European Union, 2022)
This study is a part of a project
10.2762/638991
Keywords: Graue Literatur; parliament; accession to the European Union; agri-foodstuffs; competitiveness; social development; economic development; agro-industry; foodstuff; food consumption; comparative analysis; macroeconomics; economic indicator; agricultural production; common agricultural policy; Türkiye; Western Balkans; report